1990
DOI: 10.1002/1097-0142(19900301)65:5<1242::aid-cncr2820650535>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The process of recovery from breast cancer for younger and older patients. Changes during the first year

Abstract: A representative community sample of 274 breast cancer (BC) patients from the Metropolitan Detroit Cancer‐Surveillance System was studied longitudinally during the year after their BC diagnosis. The adjustment of these patients to their disease was examined in terms of (1) the changes in their physical and mental health functioning; and (2) the factors that predict or facilitate the recovery process, including the independent and interactive effects of age. Comparison of the outcomes at 4 and 10 months after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
122
1
8

Year Published

1997
1997
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(141 citation statements)
references
References 40 publications
10
122
1
8
Order By: Relevance
“…Previous studies have suggested that age is related positively to emotional functioning (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994). In this sample, older individuals did not have better scores on the subscale psychological well-being, as measured by the QOL-CA scale, than younger patients.…”
Section: Resultscontrasting
confidence: 53%
See 4 more Smart Citations
“…Previous studies have suggested that age is related positively to emotional functioning (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994). In this sample, older individuals did not have better scores on the subscale psychological well-being, as measured by the QOL-CA scale, than younger patients.…”
Section: Resultscontrasting
confidence: 53%
“…Other investigators reported no significant relationship between age and functional status (Vinokur et al, 1990;Ganz et al, 1992;Given et al, 1994). Current trends in health care aim to reduce hospital beds in acute care units.…”
mentioning
confidence: 98%
See 3 more Smart Citations